Metabolic relationships of the isolated fractions of the pectic substances of actively growing sycamore cells - Stoddart, R. W. (1967)
1. d-Glucose and l-arabinose serve as precursors of the pectic polysaccharides of sycamore suspension-callus tissue. 2. The rates and characteristics of the incorporation of radioactive sucrose, glucose and mesoinositol by sycamore callus tissue have been compared and shown to be different. 3. The time-course of the incorporation of radioactive glucose into the major fractions within the cells has been determined. Approx. 7–10% of the radioactivity incorporated is present in the whole pectin of the cells. 4. A study of the continuous incorporation of radioactive glucose showed that the neutral arabinan–galactan fraction of the pectin quickly became saturated with the radioactive label. During the incorporation of radioactivity from a pulse of radioactive glucose the neutral fraction became progressively less labelled, with a corresponding increase in the radioactivity of the weakly acidic pectinic acid, which is known to contain neutral sugars. 5. When the cells were exposed to a pulse of radioactive l-arabinose, the label accumulated first in the neutral fraction and then after 4hr. it passed to the weakly acidic pectinic acid with a corresponding decrease in the radioactivity of the neutral fraction. 6. The product that was initially labelled during the first hour of exposure of the cells in the stationary phase to radioactive glucose was identified as an incompletely methylated galacturonan in which the radioactivity was present in the anhydrogalacturonide residues. This polysaccharide probably acts as the precursor of the polyuronide portions of both the strongly acidic and weakly acidic pectinic acids. 7. The observations are discussed in relation to the structure of the pectic substances and their function in cell growth and development. A tentative model for their metabolic relationship is put forward.